2015
DOI: 10.1002/macp.201500068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Level of Crystallinity on Melt Memory Above the Equilibrium Melting Temperature in a Random Ethylene 1-Butene Copolymer

Abstract: A strong memory effect of crystallization has been observed in melts of random ethylene copolymers even above the equilibrium melting temperature. Melt memory is correlated with self-seeds that increase the crystallization rate of ethylene copolymers. The seeds are associated with molten ethylene sequences from the initial crystals that remain in close proximity and are unable to diffuse quickly to the randomized melt state. Fast diffusion is restricted by topological chain constraints (loops, knots, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 22 publications
3
45
0
1
Order By: Relevance
“…The experimental evidence is consistent with a kinetic nature of melt memory . Even when cooling from the same melting temperature, the increase of crystallization temperature depends on molecular weight, the initial level of crystallinity or on how the standard crystalline state is prepared.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The experimental evidence is consistent with a kinetic nature of melt memory . Even when cooling from the same melting temperature, the increase of crystallization temperature depends on molecular weight, the initial level of crystallinity or on how the standard crystalline state is prepared.…”
Section: Introductionsupporting
confidence: 73%
“…The thermal protocol was repeated with lowering T 1 in successive cycles to achieve higher crystallinity levels prior to approaching heterogeneous T melt . Various T 1 were chosen within the span of the crystallization exotherm from the homogeneous melt as detailed in a prior work …”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9][10][11]15,16 However, there have been several investigations where any possible memory from such remnant crystalline domains is deliberately wiped out, but still observing melt-memory effects during second crystallization. 5,[12][13][14][17][18][19][20][21] As a classic example, Schultz observed that the maximum crystallization rate of linear polyethylene can be significantly lower if the sample was prepared at higher melt temperatures. 5 The same feature has been observed in other polymers as well.…”
Section: Introductionmentioning
confidence: 99%
“…13,17,19 Sometimes a distinction is made between two kinds of memory effects. 21 If the melt temperature is lower than the equilibrium melting temperature, some remnant crystalline domains could linger around and become responsible for melt-memory. In the other case, the melt temperature is above the equilibrium melting temperature as in the case of Schultz's experiment, and still the memory effect is manifest upon recrystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Semicrystalline polymers, such as polypropylene (PP) and polyethylene (PE), are naturally translucent or opaque, because crystals aggregate into large complexes known as spherulites . The size of these spherulites is generally larger than the wavelength of visible light resulting in light scattering and high haze of the material.…”
Section: Introductionmentioning
confidence: 99%